Carbon Sequestration and Trading - An Overview - Babu, A. Charan; Ramanjaneyulu, A. V.; Chaitanya, T.; Neelima, T. L.; Yakadri, M. (Chronicle of Bioresource Management, 2023)
Carbon is an essential element for crop growth and development. It exists in the form of CO2 in the atmosphere. It is the primary greenhouse gas (GHG) emitted due to anthropogenic activities and biological processes. Burning of fossil fuels such as coal, natural gas and oil, agricultural activities, land use changes and other natural processes are leading to the accumulation of CO2, methane, nitrous oxide and halocarbons, above threshold levels in the atmosphere. It has been linked to climate change and it’s associated consequences. These are inturn affecting the lives of human beings and other forms of life on the earth. Now, the whole scientific community is looking at carbon sequestration and carbon trading as the two most important approaches to tackle climate change, as they play a pivotal role in reducing the CO2 levels in the atmosphere either directly or indirectly.